Digitalização e correlação de perfis geofísicos de poços – Manaus – AM - FAVACHO, Giordan Maciel (2021)
The interpretative correlation of geophysical well logs located in the catchment regions of COSAMA (Companhia de Saneamento do Amazonas) was made, these wells were drilled in the city of Manaus - capital of the State of Amazonas, for the water supply of the region. The survey was carried out in some neighborhoods in the metropolitan region of Manaus, with a total of 32 wells. The most important parameters and therefore used for this work in the correlations were Gamma Ray (RG), Spontaneous Potential (SP) and Electrical Resistivity (RE). This correlation was performed in order to analyze and evaluate the lateral continuity of the geological layers most likely to be groundwater reservoirs, in order to generate high precision stratigraphic sections. It was observed the presence of interdigitations between sandy and clay layers, and within these layers it was possible to verify the probable existence of some aquifers distributed in the Manaus region, both in shallow and deeper layers of the present formation. It was also found that the relief of the city is rugged due to tectonic movements that helped in the present interdigitations. Such conclusions are of great importance for future projects and studies in the city of Manaus.